Laju Pertumbuhan Unggas 2015-2022: Katalis Ide Kreatif untuk Transformasi Agribisnis Berkelanjutan di Pulau Lombok - Nabila Arianti; Virginia Adzani; Baiq Auliya; Karina Utami; Herie Saksono (Penerbit Indocamp, 2024)
Lombok Island has great potential in developing the poultry farming sector, but an integrated approach is needed to ensure sustainable and inclusive growth. This study aims to analyze the growth pattern of the poultry population on Lombok Island and identify optimization strategies that can improve community welfare. The method used is a quantitative approach with longitudinal data from 2015 to 2022, covering types of poultry such as free-range chickens, laying hens, broilers, Manila ducks, and quail. Data was taken from the